THE STYLISTIC STRATEGIES OF FIGURATIVE LANGUAGE AND IMAGERY IN CONSTRUCTING THE MEANING OF LONGING IN HALINU NA MERIDU NARI DI TUNDUNMU BY GUSTI PRIDA GUMALA - Siti Nuraini Indriasih; Heru Prasetyo; Yinda Dwi Gustira (FKIP Universitas Lampung, 2026)
Poetry is a literary genre that employs linguistic elements to construct aesthetic value while expressing the poet's inner experiences. Although stylistic studies on poetry have been widely conducted, research examining the relationship between figurative language and imagery as fundamental elements in constructing meaning and aesthetic effects in Lampung poetry remains limited. Therefore, this study aims to describe the use of figurative language and imagery in Halinu Na Meridu Nari di Tundunmu by Gusti Prida Gumala through a stylistic approach. This study employed a qualitative descriptive method using a stylistic approach. The data consisted of the verses of Halinu Na Meridu Nari di Tundunmu by Gusti Prida Gumala. Data were collected through close reading and note-taking techniques and analyzed by identifying, classifying, interpreting, and describing stylistic elements, particularly figurative language and imagery. The findings reveal that the poem employs three types of figurative language—metaphor, personification, and hyperbole—and five types of imagery, namely visual, auditory, olfactory, kinesthetic, and tactile imagery. Metaphors are used to express longing and memories imaginatively, personification animates abstract entities to evoke emotional nuances, while hyperbole intensifies the lyrical speaker's emotions. Furthermore, the various forms of imagery create vivid sensory experiences, enabling readers to visualize, hear, smell, feel, and emotionally experience the events portrayed in the poem. The study demonstrates that the integration of figurative language and imagery not only enhances the poem's aesthetic quality but also functions as a stylistic strategy for constructing meaning, reinforcing the expression of longing, and creating profound aesthetic experiences for readers.